KELELAHAN KERJA DAN DETERMINAN PADA PENGEMUDI MINIBUS ANTAR PROVINSI JAWA-BALI TAHUN 2019 - Adytama, Steven; Muliawan, Partha (ARCHIVE OF COMMUNITY HEALTH; Vol 7 No 2 (2020): Desember 2020, 2020)
ABSTRACT Work fatigue is one of the cause in transportation problems in Indonesia that often occurs by accidents followed by high mortality rate. The aim of this research is to analyze the work fatigue in inter-province Java-Bali province minibus driver in 2019. This study is conducted using cross-sectional method with the amount total sample of interprovince Java-Bali drivers by 32 people in one company. Data retrieval is done directly after the driver arrives at the company bus base in Denpasar by interview using Japanese IFRC questionnaire and reaction timer test. The data analysis are performed using univariate and bivariate analysis with chi-square test. The results showed that all respondents didn’t experience subjective work fatigue. While objectively the respondents experienced mild work fatigue (50%), moderate work fatigue (34.38%) and heavy work fatigue (15.63%). The proportion of moderate and severe fatigue was objectively higher in the age group ?43 years and working hours >40 hours/week (p<0.05) while the marital status, nutritional status and years of service did not have a significant difference (p>0.05). It was suggested that minibus driver reduce working hours to one round trip in a week on long distance routes conduct a medical check-up program and place routes closer to the minibus driver ?43 years old.